Video analysis of anterior cruciate ligament injuries in sumo wrestling. Issue 4 (27th March 2011) - Goshima, K; Kitaoka, K; Shima, Y; Nakase, J; Takahashi, R; Tsuchiya, H
Abstract : Background: Sumo is one of the traditional Japanese contact sports. Many sumo wrestlers suffer knee joint injuries, especially anterior cruciate ligament (ACL) injuries. ACL injuries can lead to serious consequences for injured sumo wrestlers. Therefore, Understanding the mechanisms of these injuries is crucial to prevent ACL injuries. Objective: To describe the mechanisms of ACL injuries in sumo wrestling. Design: Descriptive video analysis. Methods: Eight videotapes of ACL injuries from seven professional sumo wrestlers and one high school student were collected. Four medical doctors and two physical therapists systematically analyzed these videos to describe the injury mechanisms and playing situations. We estimated knee flexion, internal/external rotation, and valgus/varus position at the time when the ACL ruptured. Results: Two main mechanisms of ACL injuries in sumo wrestling were identified. Five knees had been injured while the wrestlers tried to make a stand at the edge of the ring, and three knees had been injured when the wrestlers tried to stay on their feet before they were thrown by their opponents. All of the mechanisms for ACL injuries were non-contact injuries; they were not caused by direct external impacts. The injuries occurred when the foot was planted and firmly fixed at the edge of the ring or the floor. In all cases, the foot was externally rotated. The knee was in flexion (the mean angle was 57.2°) and valgus, combined with internal rotation of the tibia relative to the femur. Conclusion: Many of the sumo wrestlers suffered ACL injuries when they tried to make a stand at the edge of the ring. The mechanism of ACL injuries in sumo wrestling appeared to be non-contact injuries.